Characteristics of the first immunocompromised patients to receive sipavibart as an early access treatment for COVID-19 pre-exposure prophylaxis in France - Paul Loubet; Benjamin Gaborit; Mathilde Salpin; Hèlene Gardeney; Ilies Benotmane; Thomas Systchenko (Human Vaccines & Immunotherapeutics)
France was the first country to grant Sipavibart (AZD3152, an investigational long-acting monoclonal antibody) as a COVID-19 pre-exposure prophylaxis treatment in immunocompromised individuals in December 2023. The first patients to receive Sipavibart had different profiles, but they were all highly immunocompromised with frequently associated hypogammaglobulinemia and other chronic conditions. No adverse event was reported.